PERANCANGAN BRANDING TROWULAN MELALUI SITUS PURBAKALA SEBAGAI UPAYA PELESTARIAN WARISAN BUDAYA LOKAL - Wicaksono, Satrio Arif; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: The aim of the design was to Trowulan branding preserve local cultural heritage. Research conducted using qualitative research methods, namely by doing interviews, observation, documentation, library and study to get the data used as the supporter of the creation of the concept design of branding. The data were analyzed by using multiple stages, namely the reduction of the data, the presentation of data, and conclusions. From the analysis of the data found few keyword refers to the communication strategy of branding that will be used to achieve the target the intended audience. After analysis of the data, the found a concept or design branding keywords i.e. "Grandeur". The description of the concept of "Grandeur" is a form of real will be the heritage of Majapahit in Trowulan. In this case the "Grandeur" or oversize evidence of Majapahit in Trowulan existing directed at how to maintain the local cultural heritage in the form of cultural heritage that is packaged by making cultural heritage that exists in Trowulan as a point of interest in the various media used to promote Trowulan. The result of the design of this branding is to preserve local cultural heritage in trowulan formerly is the administrative center of the Majapahit KingdomKeywords: Branding, Trowulan, cultural heritage, Local cultural heritage